IMPLEMENTATION OF WATER SUPPLY SUPERVISION IN CLASS 1 PORT HEALTH OFFICE IN JUANDA AIRPORT WORKING AREA, SURABAYA - Rizky Nugrahanik; Bangun Cahyo Utomo (The Indonesian Journal of Public Health, 2021)
ABSTRACTThe provision of clean water in the Class 1 Surabaya Port Health Office is supervised in accordance with the existing regulations to identify sources that could potentially cause pollution and prevent the occurrence of illness caused by unstandardized water quality and unsafe water supply. This study aimed to describe the implementation of clean water supply supervision in the Class 1 Surabaya Port Health Office in the Juanda Airport working area, Surabaya. This was an observational study which analysis was descriptive in nature. The clean water was tested for physical, chemical, and microbiological parameters, and the results showed that the water quality was in accordance with the Regulation of the Indonesian Ministry of Health No. 416 of 1990 about the Terms and Monitoring of Water Quality. However, the result from the simple chemical inspection test of the water showed that it did not fulfil health standards i.e., the residual chlorine score not equal to 0 (zero). It is suggested that more attention and supervision are conducted by water management authorities to ensure the standard residual chlorine level of 0 (zero). Additionally, expired reagents or reagents that have already changed color should not be used as it will affect the parameters tested. Keywords: Quality of clean water, clean water supply facilities, water sampling process